2020
DOI: 10.1136/bmj.m2177
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism: update on management and controversies

Abstract: Pulmonary embolism is a common and potentially fatal cardiovascular disorder that must be promptly diagnosed and treated. The diagnosis, risk assessment, and management of pulmonary embolism have evolved with a better understanding of efficient use of diagnostic and therapeutic options. The use of either clinical probability adjusted or age adjusted D-dimer interpretation has led to a reduction in diagnostic imaging to exclude pulmonary embolism. Direct oral anticoagulation therapies are safe, effective, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 168 publications
(253 reference statements)
1
103
0
23
Order By: Relevance
“…Moreover, an activated coagulation state in tumor tissues could form a fibrin matrix to shield tumor cells against the immune attack and foster tumor growth, which finally contributes to poor cancer prognosis [ 27 , 28 ]. Previous studies indicated that D-dimer, a degradation product produced by hydrolysis of fibrinolytic protein, could assess secondary fibrinolytic activity and hyper-coagulability [ 29 ]. Meanwhile, the INR system, applied to standardize PT, could evaluate the “extrinsic coagulation pathway” in individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an activated coagulation state in tumor tissues could form a fibrin matrix to shield tumor cells against the immune attack and foster tumor growth, which finally contributes to poor cancer prognosis [ 27 , 28 ]. Previous studies indicated that D-dimer, a degradation product produced by hydrolysis of fibrinolytic protein, could assess secondary fibrinolytic activity and hyper-coagulability [ 29 ]. Meanwhile, the INR system, applied to standardize PT, could evaluate the “extrinsic coagulation pathway” in individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The types of treatment in acute pulmonary embolism vary with the clinical presentation. Anticoagulation and thrombolysis are the standard means of treatment for acute pulmonary embolism, but these are to be reserved for hemodynamically stable patients [ 18 ]. Clinical data suggest that patients being treated by thrombolysis are at a higher risk of death by increased risk of major hemorrhage and a high probability of pulmonary embolism recurrence compared with patients treated by pulmonary embolectomy [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Models such as the Pulmonary Embolism Severity Index (PESI) and the simplified-PESI (sPESI) risk prediction scores provide a tool for identification of low-risk and high-risk patients. 22 According to ESC guidelines, treatment of high-risk acute PE includes early oxygenation in the form of ventilation if required, ensuring haemodynamic stability, and management of right heart failure, including need for vasopressors and advanced life support in severe cases. 23 The CHEST guidelines provide specific recommendations regarding choice of anticoagulant with respect to phase of VTE treatment.…”
Section: Role Of Anticoagulants In Pementioning
confidence: 99%